STRATIFIKASI PENDIDIKAN ISLAM: ANALISIS KEPUSTAKAAN TENTANG REPRODUKSI KELAS SOSIAL DI SEKOLAH ISLAM MODERN - Alifatur Rodziah, Dinda; Jannah, Royanatul; Zahro, Lutfiatuz; Khairul Anam, Rifqi (As-Sulthan Journal of Education, 2026)
This article explores social inequality within Islamic education, particularly focusing on the divide between elite Islamic schools catering to the upper class and modest Islamic schools serving ordinary communities. The study aims to conceptually examine how this disparity affects the core Islamic values of social justice and equality in education. Employing a library research method with a descriptive qualitative approach, data were collected and analyzed from relevant academic literature. The findings reveal that while the modernization of Islamic education has contributed positively to improving quality and professionalism, it has also generated negative effects such as commercialization and the loss of autonomy in grassroots Islamic schools. The study argues that reform in Islamic education is essential to ensure inclusivity and equity in access to quality learning. Efforts such as scholarship programs, cross-subsidization, and strengthening of madrasah institutions are crucial to restore the fundamental purpose of Islamic education as a means of enlightenment and empowerment grounded in social justice.